Exploring the Impact of Mastery Goals on Foreign Language Reading Enjoyment via Control and Value Appraisals - Abd Halim, Hasliza; Wang, Yuhan (Forum for Linguistic Studies, 2025)
Existing studies show that foreign language reading enjoyment plays a vital role in language learning. However, few studies have investigated its antecedents. With reference to control-value theory, this research addressed how mastery goals contribute to foreign language reading enjoyment, considering control and value appraisals as mediating variables among undergraduate EFL learners in China. 618 EFL undergraduate learners from three universities across China participated in this investigation. A composite questionnaire was administered, including demographics and the completed scales of mastery goals, control appraisal, value appraisal, and foreign language reading enjoyment. Pearson correlation analysis illustrated the positive influence of mastery goals on the two appraisals and foreign language reading enjoyment. Then, a parallel mediation analysis was conducted, assessing the extent to which control and value appraisals mediated the link between mastery goals and foreign language reading enjoyment. With gender and academic achievement being controlled, the analysis yielded a total direct effect (β = 0.447), together with the indirect effect (β = 0.434), suggesting that control and value appraisal work in parallel to fully mediate the relationship. Moreover, value appraisal played a more dominant role, accounting for 77% of the total indirect effects. The findings lent support to control-value theory and broadened its scope to encompass specific subdomains within EFL learning contexts. It is expected to benefit EFL instructors, learners, and policymakers.